Pengembangan Model Kriteria Ketuntasan Minimal melalui Prototipe Buku untuk Meningkatkan Kemampuan Guru di Kabupaten Labuhanbatu - Nur Salamah Siregar; Rosmawati Harahap; Titi Chandrawati (Mahesa Research Center, 2022)
This article aims to determine the feasibility of the KKM model based on the book prototype in improving teachers' teaching abilities, to find out the process of developing the KKM model using the textbook prototype to improve teachers' teaching skills, and to determine the effectiveness of developing the KKM model in improving teaching skills through the KKM book prototype. The problem is focused on developing a minimum completeness criteria model through a book prototype to improve the ability of teachers. In order to approach this problem, a theoretical reference from the Ministry of National Education is used. Minimum completeness criteria must be included in the learning outcomes report as a reference in addressing student learning outcomes. The data were collected through a questionnaire technique by distributing questionnaires to fourth and fifth grade teachers. This data collection aims to determine the need for prototype books and information that is used as material for product preparation and analyzed qualitatively. This study concludes that the 8 R & D steps in developing the KKM book prototype are better used to increase teacher effectiveness in determining the minimum completeness criteria (KKM) in elementary schools at the beginning of the school year.